2015
DOI: 10.1007/jhep02(2015)050
|View full text |Cite
|
Sign up to set email alerts
|

Marginally deformed Starobinsky gravity

Abstract: We show that quantum-induced marginal deformations of the Starobinsky gravitational action of the form R 2(1−α) , with R the Ricci scalar and α a positive parameter smaller than one half, can generate sizable primordial tensor modes. We also suggest natural microscopic sources of these corrections and demonstrate that they generally lead to a nonzero and positive α. Furthermore we argue, that within this framework, the scalar spectral index and tensor modes probe theories of grand unification including theorie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 28 publications
(42 reference statements)
6
55
0
Order By: Relevance
“…k 2 ∼ R (see also [41]). In a recent investigation a similar approach has been successfully applied to study the quantum gravity modifications of the Starobinsky model [42] (see also [43][44][45][46][47][48] for other examples of quantum deformed quadratic gravity inflationary models).…”
Section: Introductionmentioning
confidence: 99%
“…k 2 ∼ R (see also [41]). In a recent investigation a similar approach has been successfully applied to study the quantum gravity modifications of the Starobinsky model [42] (see also [43][44][45][46][47][48] for other examples of quantum deformed quadratic gravity inflationary models).…”
Section: Introductionmentioning
confidence: 99%
“…In the light of the possibility that r can be larger than the Starobinsky model prediction of r ∼ 0.003, generalisations of the Starobinsky model are of interest. The quantum correction on φ 4 -potential in Jordan frame was studied in [102,103,104,105] where they have shown the equivalence of the ξφ 2 R + λφ 4(1+γ) model with 1 M 2 R β model. The generalized Starobinsky model with R p correction has been studied in the ref.…”
Section: +007mentioning
confidence: 99%
“…(1.2), with 1 < n < 2 according to Ref. [16]) during the Universe evolution from GUT scales to the transition time t * . The latter characterizes the instant in which the Universe passes from the cosmic evolution described by f (R) cosmology to the cosmic evolution described by the standard cosmological model (see below).…”
Section: Field Equations In F (R) Gravitymentioning
confidence: 99%
“…[14,15] show that the Starobinsky model is in good agreement with the BICEP2 data. Moreover, sizable primordial tensor modes can be generated in (marginally deformed) models of the form (1.2), provided 1 < n < 2 [16] (more specifically in [16] it is shown that if inflation is driven by f (R) gravity, then a natural form for this function is (1.2), where the value of n could be related to the microscopic theory dictating the trace-log quantum corrections). The main point is to rewrite the f (R) action in the Einstein frame, which implies the appearance of a scalar field.…”
Section: Introductionmentioning
confidence: 99%